Role of Elicitors in Inducing Resistance in Plants against Pathogen Infection: A Review. (28th January 2013) - Thakur, Meenakshi; Sohal, Baldev Singh
Abstract : Disease control is largely based on the use of fungicides, bactericides, and insecticides—chemical compounds toxic to plant invaders, causative agents, or vectors of plant diseases. However, the hazardous effect of these chemicals or their degradation products on the environment and human health strongly necessitates the search for new, harmless means of disease control. There must be some natural phenomenon of induced resistance to protect plants from disease. Elicitors are compounds, which activate chemical defense in plants. Various biosynthetic pathways are activated in treated plants depending on the compound used. Commonly tested chemical elicitors are salicylic acid, methyl salicylate, benzothiadiazole, benzoic acid, chitosan, and so forth which affect production of phenolic compounds and activation of various defense-related enzymes in plants. Their introduction into agricultural practice could minimize the scope of chemical control, thus contributing to the development of sustainable agriculture. This paper chiefly highlights the uses of elicitors aiming to draw sufficient attention of researchers to the frontier research needed in this context.